Stability assessment methods of technological processes - Tchigirinsky Julius (EDP Sciences, 2021)
Ensuring the stability of quality indicators and product accuracy in modern conditions requires not only classical production measures but also organizational arrangements, which deals with clarifying and modernizing the conceptual apparatus. The study analyzes the methods for assessing the stability of machining, established in the standard process documents regulating the issues of product quality management in mechanical engineering, and reveals the ambiguity of the term ‘stability’ relating to processes under transition to the arrangement of digital production and the use of equipment with adaptive control. The Fisher criterion can be used for quantitatively analyzing the stability of processes under statistical control.